10x=x 9x=0 x=0
3x2 - 10x - 8 = (3x + 2) (x - 4)
Depends on the value of x if x is 1 then 10x + 20 = 30 if x is 2 then 10x + 20 = 40 if x is 3 then 10x + 20 = 50 if x is 4 then 10x + 20 = 60 if x is 5 then 10x + 20 = 70 if x is 10 then 10x + 20 = 120 And so on
7x + 8 = 10x - 2 ∴ 3x = 10 ∴ x = 10/3
mansion
Y = 10x 10x = 40 y = 40
10x 2x divide 2x equals?
15
10x and 6y are terms of an algebraic expression
10x + 3 = 15 10x = 15 - 3 10x = 12 x = 1.2
-10x-6 = -12 -10x = -12+6 -10x = -6 x = 3/5
5x + 4 = 10x - 5 10x - 5x = 4 + 5 5x = 9 x = 1.8
10x - 5 = 2510x = 30x = 3
11x = 10x-19 Subtact 10x fromboth sides:- x = -19
-10x = x-33 -10x-x = -33 -11x = -33 x = 11
10x=x 9x=0 x=0
To solve the equation 10X = 2.7, you need to isolate the variable X. Start by dividing both sides of the equation by 10 to get X alone. This gives you X = 2.7/10, which simplifies to X = 0.27. Therefore, the solution to the equation 10X = 2.7 is X = 0.27.